2021
DOI: 10.3389/fmed.2021.594043
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Adverse Events Reports for Angiotensin-Converting Enzyme Inhibitors: Data Mining of the FDA Adverse Event Reporting System Database

Abstract: Because of contradictory evidence from clinical trials, the association between angiotensin-converting enzyme inhibitors (ACEIs) and lung cancer needs further evaluation. As such, the current study is to assess disproportionate reporting of primary malignant lung cancer among reports for ACEIs submitted to the FDA adverse event reporting system utilizing a pharmacovigilance approach. We conducted a disproportionality analysis of primary malignant lung cancer adverse events associated with 10 ACEIs by calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Based on the search strategy, 2400 records from the databases were screened, of which 392 duplicated records and 1976 records did not meet the inclusion criteria and were excluded. Finally, 11 clinical studies [12][13][14][23][24][25][26][27][28][29][30], including seven cohort studies [12,14,23,[26][27][28]30] and four case-control studies [13,24,25,29], conducted between 1988 and 2020 were included in the meta-analysis (Fig. 1).…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the search strategy, 2400 records from the databases were screened, of which 392 duplicated records and 1976 records did not meet the inclusion criteria and were excluded. Finally, 11 clinical studies [12][13][14][23][24][25][26][27][28][29][30], including seven cohort studies [12,14,23,[26][27][28]30] and four case-control studies [13,24,25,29], conducted between 1988 and 2020 were included in the meta-analysis (Fig. 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…One study [29] did not voluntarily report mean follow-up time, based on a post hoc analysis of the database it used, we found that its mean follow-up time was 1.73 years, but the study was not included in the follow-up time subgroup analysis because some follow-up data were missing from the database. The other included studies in the subgroup analysis voluntarily reported the follow-up time of 3.6-9 years.…”
Section: Meta-analysis Of Aceis and Risk Of Lung Cancermentioning
confidence: 97%
See 1 more Smart Citation
“…The FAERS database Quarterly Data Files (January 1, 2019, to November 4, 2021) were used. OpenVigil FDA, a validated pharmacovigilance tool, was adapted to access the FDA drug-event database with the additional openFDA drug mapping and duplicate detection functionality (18)(19)(20).…”
Section: Data Sources and Study Variablesmentioning
confidence: 99%
“…Compared to other international databases for spontaneous AE reporting, FAERS has several distinctive characteristics, including the heterogeneous catchment area (to broaden the generalization of findings), the public access to raw data that can be downloaded in a format suitable for customized analysis ( Antonazzo et al, 2020 ). Data mining from the FAERS pharmacovigilance source can be utilized to evaluate drug safety, such as identifying rare or new AEs ( Meng et al, 2021 ) and quantitatively detecting drug-drug interactions (DDIs) ( Oshima et al, 2018 ; Antonazzo et al, 2020 ). The present study aimed to detect safety signals between the concomitant use of PI and FXaI (both as a drug class and as a single agent) and the appearance of PN.…”
Section: Introductionmentioning
confidence: 99%